Carcinogenesis and therapeutics: the microbiota perspective - Tsilimigras, Matthew C. B. (Nat Microbiol, 2017)
Cancer arises from the acquisition of multiple genetic and epigenetic changes in host cells over the span of many years, promoting oncogenic traits and carcinogenesis. Most cancers develop following random somatic alterations of key oncogenic genes, which are favoured by a number of risk factors, including lifestyle, diet and inflammation. Importantly, the environment where tumours evolve provides a unique source of signalling cues that affects cancer cell growth, survival, movement and metastasis. Recently, there has been increased interest in how the microbiota, the collection of microorganisms inhabiting the host body surface and cavities, shapes a micro-environment for host cells that can either promote or prevent cancer formation. The microbiota, particularly the intestinal biota, plays a central role in host physiology, and the composition and activity of this consortium of microorganisms is directly influenced by known cancer risk factors such as lifestyle, diet and inflammation. In this Review, we discuss the pro- and anticarcinogenic role of the microbiota, as well as highlighting the therapeutic potential of microorganisms in tumourigenesis. The broad impacts, and, at times, opposing roles of the microbiota in carcinogenesis serve to illustrate the complex and sometimes conflicted relationship between microorganisms and the host—a relationship that could potentially be harnessed for therapeutic benefits.